Implication of Career Development And Demograpic Factors on Quality of Work Life - Zulkarnain, -; Mahamood, Yahaya; Omar, Fatimah (Faculty of Psychology, Universitas Gadjah Mada, 2010)
The objective of this research is to study the implication of career development and demographic factors on quality of work life. The research was done cross sectional, by conducting 429 subjects who work in public service. Data was collected from a set of questionnaires which consists of scale of quality of work life, scale of career development and bio data. The result of Pearson correlation analysis indicated positive and significant correlation between career development and quality of work life. The correlation indicated that the positive perception of career development, the higher of quality of work life. Also, the Point Biserial correlation indicated demographic factors such as; sex, age, education, length of service and marital status showed positive and significant with quality of work life. These findings contribute to an understanding of ways by top management in attempts to attain a quality of work life between the needs of the employees and the needs of the organization.